Non-syndromic bilateral lower lip pits: A case report and literature review - Ulaganathan, Prabhakar; Balasubramanian, Sankararaman (Indian Journal of Case Reports, 2025)
This case report describes a rare occurrence of non-syndromic lower lip pits. The 16-year-old female patient had bilateral pits on the lower lip vermilion, without any other associated abnormalities, which sets this case apart from the syndromic lip pits seen in Van der Woude syndrome. The report outlines the clinical features, diagnostic evaluation, and chosen treatment approach, emphasizing the importance of recognizing and distinguishing isolated lip pits from syndromic presentations.